Answer:
![\int _3^42x^2+9dx=(101)/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/kw1nber2orpb2k2a9zqv2bena8ixnwyerq.png)
Explanation:
The Fundamental Theorem of Calculus says,
Suppose
is a continuous function on
and also suppose that
is any anti-derivative for
![\int_{{\,a}}^{{\,b}}{{f\left( x \right)dx}} = \left. {F\left( x \right)} \right|_a^b = F\left( b \right) - F\left( a \right)](https://img.qammunity.org/2020/formulas/mathematics/college/gx1wfaf7seqqbve8td6sygnq2cawy8uq3u.png)
Using the above definition, we can evaluate the definite integral
![\int\limits^4_3 {2x^2+9} \, dx](https://img.qammunity.org/2020/formulas/mathematics/college/f1h6ldpkvl37qvfo3nlwjustin6a4r1vx6.png)
First,
![\int _3^42x^2+9dx=\int _3^42x^2dx+\int _3^49dx](https://img.qammunity.org/2020/formulas/mathematics/college/npfq1lvuixrnhofe58ux736bcgsm7jcydl.png)
Evaluate the integral
![\int _3^42x^2dx=2\cdot \int _3^4x^2dx\\\\\mathrm{Apply\:the\:Power\:Rule}:\quad \int x^adx=(x^(a+1))/(a+1),\:\quad \:a\\e -1\\\\2\left[(x^(2+1))/(2+1)\right]^4_3=2\left[(x^3)/(3)\right]^4_3\\\\\mathrm{Compute\:the\:boundaries}:\\\\2((4^3)/(3)-(3^3)/(3)) =2\cdot (37)/(3)= (74)/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/r2d6ses48k8pl1ezskhqqwe0zu5pz3ie72.png)
and the integral
![\int _3^49dx=\left[9x\right]^4_3=9(4)-9(3)=9](https://img.qammunity.org/2020/formulas/mathematics/college/6inh407un0q1ghi1pjiw4u86or3f601f43.png)
Finally, we get that
![\int _3^42x^2+9dx=(74)/(3)+9=(101)/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/v5tweu78isrrzpu5ejvagj7mhhmp02xaa8.png)